(untitled) (Advances in Military Technology, 2022)
This article proposes a comparative method of a possible analysis technique of the detection area, in the Electronic Intelligence (further ELINT) system, regarding the values of detection probability PD, false alarm probability PF and the change of output within ELINT source PZ. By this analysis it is assumed that there is a monitoring of mobile ELINT sources, which are located on the margin of ELINT system radio horizon, whereby it is necessary to carry out the radio-locating of these sources in the main lappet of directivity pattern source axis and ELINT device.